Virtual distortional rehabilitation by composite and contact beams of a reinforced concrete building based on mixed testing. - Torres Montes de Oca, Carlos Alberto; Segovia Huitrón, Miguel Angel; Prado González, Roberto; Alba Campos, Angel Gilberto (Revista ALCONPAT, 2025)
The objective of this research is to simulate, by means of virtual modeling, the recovery of the distortional stability of a reinforced concrete building by means of composite and contact beams. The methodological procedure is based on previous studies such as pathological auscultation, concrete coring, sclerometry, environmental vibration tests, soil mechanics and generation of mathematical models. The analyses and studies are carried out in accordance with national and international standards. The model representing the current state of the structure was numerically calibrated. The results indicate that by using composite section beams for the reinforcement of the system, greater stiffness is obtained in the superstructure compared to contact beams.